ANALISIS PERCEIVED USEFULNESS DAN PERCEIVED EASE OF USE TERHADAP MINAT MENGGUNAKAN MOBILE PAYMENT (Studi pada Pengguna Aplikasi Pembayaran OVO) - Emi Amelia; Ratih Hurriyati (Universitas Airlangga, 2022)
The acceptance of new technology has become one of the most important areas in information technology. The impact of low consumer interest in using a non-cash payment system (online) is an important problem because it is related to someone's decision to use a non-cash payment system. Currently, consumers have not used the services offered by mobile payment optimally. Efforts to predict a person's interest or consumer behavior in technology acceptance are seen from the perceived usefulness and perceived ease of use. This study aimed to determine the description of behavioral intention, Perceived Usefulness, and perceived ease of use using OVO mobile payment application technology by consumers. The type of research used is descriptive verification, and the method used is an explanatory survey with a purposive sampling technique with a sample of 150 respondents. The data analysis method used is validity and reliability test, path analysis, multiple correlation analysis and coefficient of determination analysis. They are testing this hypothesis through the F test for simultaneous and partial T test using the SPSS 18.0 for windows program. The results showed that simultaneously Perceived Ease of Use and perceived ease of use had a significant effect on behavioral intention of 60.8% and partially, Perceived Ease of Use had a greater influence, namely 60.06%, than Perceived Usefulness of 1.44% to behavioral intentions.